Resolving jurisdictional conflict on waqf issues in Malaysia - Abas, Afridah; Ahmad Bustami, Tajul Aris; Wan Muhammad, Ramizah; Muhammad, Laeba; Ibrahim, Norliah (Ahmad Ibrahim Kulliyyah of Laws, IIUM, 2025)
This paper highlights the role of endowment governance, along with its underlying principles and rules, in regulating the work of waqfinstitutions. It promotes oversight,integrity, and transparency, thereby building trust among stakeholders, especially donors, who can dedicate their wealth with confidence that their stipulations will be respected. Using inductive and analytical methods, the study underlines the positive impact of governance on sectoral development and institutional performance. The findings suggest that applying governance principles to waqf contributes to safeguarding donors' intentions, ensuring proper management of endowments, and investing their returns in ways that benefit beneficiaries and secure the long-term development of waqf.